The Truth Behind Practices: Wittgenstein, Robinson Crusoe and Ecclesiology - Insole, Christopher J. (Studies in Christian ethics, 2007)
The Wittgensteinian claim that meaning is immanent to 'practices', influential in contemporary theology, is capable of two readings: the first takes `practice' to refer to the social activities of actual communities; the second implies no more than a way of going on that is in principle communicable. The first reading is palpably unattractive, both philosophically and exegetically; the second reading is much less ambitious, providing a plausible critique of empiricist theories of meaning. I suggest that it is the first implausible reading that is often at work in theological appropriations of Wittgenstein, such as we find in Stanley Hauerwas. I fill-out this claim by exploring — with an ear to Scripture — the implications for ecclesiology of adopting either of the two readings. I conclude by raising the alarm about two dangers: of being too Wittgensteinian in some respects, and not Wittgensteinian enough in others.